ANALISIS DETERMINAN POSITIVE DEVIANCE STATUS GIZI BALITA DI WILAYAH MISKIN DENGAN PREVALENSI KURANG GIZI RENDAH DAN TINGGI - Sakri Sab'atmaja; Ali Khomsan; Ikeu Tanziha (Jurnal Gizi dan Pangan, 2010)
The aim this study was to analyze the determinant of positive deviance nutritional status of under five year old children in poor areas with low and high prevalence of undernutrition. Cross sectional study was conducted in the study using secondary data analysis taken from Basic Health Research 2007 in four provinces with determination samples criterias of high poverty levels according BPS 2009 (>14.15%) and low and high prevalence of undernutrition (+18.4%) which were analyzed through quadrants. The number of samples was 3.494 under five year old children from poor families. The significancy relations among variables were measured using Pearson's correlation and path analysis to analyze the determinants. The results, the determinant of positive deviance were income through mother's characteristics, health upbringing, and health status, the four provinces had the same determinants pathway (β=0.0451), with mother's characteristics (p<0.05) and health upbringing (p<0.05) as the significants variables. The conclusion was that mother with better characteristics in families who were able to manage income better, tended to practice better health upbringing which increase children's nutritional status. These factors determine the poor families living in the poor areas could have well nourished under five year old children rather than other families in the same economic condition. Key words: positive deviance, undernutrition, nutritional status.